Annual Report on Exchange Arrangements and Exchange Restrictions 1999. (Annual Report on Exchange Arrangements and Exchange Restrictions; 1999, 1999)
The exchange and trade systems of IMF member countries are presented in this comprehensive volume in a tabular format. There is expanded coverage of the regulatory framework for capital movements. The information generally relates to the end of 1998 but also covers significant developments in early 1999. Published in September.